Microstructure evolution during solution annealing of an Al–Zn–Mg–Cu alloy with La additions - Tilen Balaško; Aleš Nagode; Jiehua Li; Jožef Medved (Scientific Reports)
Abstract The high-strength 7xxx Al alloys are frequently used due to their excellent properties. To achieve these properties, heat treatment is crucial. In this study, the influence of La on the microstructure evolution of Al–Zn–Mg–Cu alloys during solution annealing, the first step of heat treatment, was investigated. The results showed that La additions significantly affect the microstructure by increasing in the eutectic solidus temperature, influencing the melting enthalpy of Mg2Si/LaAlSi, promoting the formation of LaAlSi and reducing Mg2Si, increasing the melting enthalpy of α-Al, shortening the time to reach the eutectic melting peak and preventing a significant increase in grain size. A 10 h solution heat treatment was recommended, with minimal benefits after 12 h. 0.15 wt% La was the minimum to prevent an increase in grain size. La altered the Al45Cr7 phase and formed a new Al20Cr2La phase with larger dimensions and sharper edges. Faster cooling rates refine the grain size due to precipitation along the grain boundaries. The content of the T-phase (Mg32(Al, Cu, Zn)49) decreased with increasing annealing time. Prolonged annealing promoted the diffusion of Mg and Zn from the eutectic phases, which led to their dissolution in the matrix. Zn diffused out first, followed by Mg. Prolonged annealing favored the formation of the Al7Cu2Fe phase over the Al13Fe4 phase.